Scientists' opinions on immunity certificates: Evidence from a large-scale survey among more than 12,000 scientists - Iván Aranzales; Ho Fai Chan; Reiner Eichenberger; Rainer Hegselmann; David Stadelmann; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
The challenges posed by the COVID-19 pandemic have prompted scientists from different fields to evaluate whether the use of immunity certificates would allow for a safer and faster return to normality. This policy has been recently implemented by Israel (Green Pass) and similar legislation is currently being proposed at the European Commission. We show that there is a high level of scientific consensus regarding the benefits of such a passport for public health and the economy, while its effects on fairness and inequality remain controversial. In general, it is essential to understand the opinions of the scientific community regarding this controversial topic, so we may address shortcomings and tackle both the current and any possible future pandemics humanity may face.
Keywords: 330